A study of students' learning approaches and their engagement with the context of learning the case of University of the Philippines College of Dentistry - Adarve, Ranier M. (2002)
Most educational researches on teaching and learning process give considerable attention to curriculum, evaluation and teacher's effectiveness but little attention is given on how students approach the learning task. Since the aim of teaching is facilitation of learning, it is suggested that students' perspective must be considered. This study therefore, was aimed at determining the learning approach profile of students of University of the Philippines College of Dentistry and explored the manner in which students interact with the various context of learning context. One hundred forty-seven (147) students participated in the study. The number represents te total number of the population (100% response rate). The study utilized Biggs' Study Process Questionnaire to determine the learning approach profile of the students. Using SPQ Manual, data were scored and interpreted in comparison with the norms. At the same time, purposive sampling of students was done. Twenty students were interviewed to describe the characteristics of the context of learning associated to the development of varying learning approaches. Results of the learning approaches revealed the following: Second Year and Third Year Female groups were having Deep Predominant profile. They learn with the intention to understand. First Year Male group has Surface Predominant Profile. This group primarily utilizes rote learning strategy and learn without deep understanding. First Year Female, Second Year Male and Fourth Year Male groups were having Surface-Achieving Profile, a profile that belongs to students who want to achieve but adopt a surface approach and usually unsuccessful. Third Year Male group had Low-Achieving Profile, in which students' motive to avoid failure is stronger than their need to achieve academic success, and lastly, the Fourth Year Female group as having High Deep-Motive profile. These students have high interest in searching for meaning and personal relevance, however, they lack strategy to achieve high marks. Results of the interview, on the other hand, highlighted specific perception of students on the context of learning particularly the context that includes students' interest, knowledge base and previous experience, effects of assessment, experience with teaching and teachers and effects of courses, departments and institution. These perceptions of the students provided the evidence that explains the influence and effects of context of learning to students learning approaches. The study also provided specific recommendations for future studies on students' learning approaches. Such studies are of critical importance to understanding teaching and learning process from students' perspective.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Learning strategies